Determinants of purchase intention in cafeterias: Intervening effects of customer satisfaction and gender - Ramli, Mona Fairuz; Mhd Yusak, Nurul Aqilah; Ramli, Nor Azlinda; Alekam, Jamal Mohammed Esmail; Nik Mat, Nik Kamariah (2014)
Several studies in the field of branding management, customer behaviour have mentioned that there are variables related to effect customer brand loyalty such as perceived quality, brand awareness, brand equity, among others.However, few studies have attempted to consider the influence of brand image and brand personality.Even if any, they have reported conflicting findings.This paper proposes to examine the relationship between brand image and brand personality on brand loyalty.